The spread of Rumors through Social Networking Sites and their effects on Social Security. (Raparin Journal of Humanities (RJH), 2024)
Social media have been widely spread due to their interactivity، ease، and speed of access to news and information، which made them a fertile environment for the growth of lies and paved the way for rumors to spread and have become one of the most dangerous weapons of fourth generation wars in spreading discord and chaos and destabilizing the security and social stability of countries. This study came to address the spread of rumors through social media platforms and their effects on social security. I used the descriptive analytical method.The study concluded with a set of results، most notably: Transcending the concept of Social media from communication media for social communication to an electronic environment qualified to spread rumors. In addition to the multiplicity of types of rumors and the varying motives and gratifications of their promoters from one society to another. Among the most prominent negative effects of the spread of rumors on Social media is that they work to spread chaos، disintegrate society، spread fear and anxiety in the hearts of members of society، and also work to spread terrorism and threaten the internal stability and social security of states. In Iraq and the Kurdistan Region، the spread of rumors through social media has led to the destabilization of civil and community peace، provoking strife، deepening internal disputes، losing confidence in officials and community leaders، as well as losing a sense of tranquility and security، spreading the values of violence and a culture of hatred، and provoking sectarian or ethnic strife among the components of Iraqi society. Hence the threat to security and social stability in Iraq and the Kurdistan Region.The study recommended the importance of developing a preventive media strategy to educate community members about the danger of rumors on the social security of Iraq. The need for the media to adopt credibility and transparency in reporting events، open the way for the masses to express their views on various issues، and create an independent media and research center to monitor and analyze rumors. And the application of deterrent penalties for those who spread rumors that pose a threat to social security in Iraq and the Kurdistan Region.